Implementación de contabilidad de servicios en turismo Saraurku Cia. Ltda., del cantón Saraguro periodo mayo-julio 2014 - Lozano Sarango, Zoila Cecilia (2015)
The present research work entitled AUDIT MANAGEMENT AREA DE SALUD No.1 Loja province DURING THE PERIOD 01 JANUARY TO 31 DECEMBER 2012, aims to develop overall audit procedures to evaluate the proper functioning of the entity and the services it provides in relation to the management, control and operations activities related to components such as human resources, health services, prevention and health that run in the area of health today considered strategic. With regard to the specific objectives has evaluated compliance with the laws issued by the Ministry of Finance, Ministry of Health and the Comptroller General also has presented the audit report, relevant, pertinent and sufficient, with recommendations and comments, capable of correcting the flaws that were encountered during the execution of the management audit and deliver them to the management of the institution and finally the application is set percentage indicators in implementing projects and programs implemented in the year 2012. Also to make this research work methods and techniques were used which allowed for a performance audit in the Health Area No.1, such as the scientific method to collect and consolidate appropriate theoretical and